Organizational Agility in Educational Setting: A Case Study of Sekolah Murid Merdeka - Laksmi M Wijayanti; John T Purba; Evo S Hariandja; Rosdiana Sijabat (Jurnal Studi Guru dan Pembelajaran, 2021)
Agility becomes the most significant dimension in facing the Volatility, Uncertainty, Complexity and Ambiguity (VUCA) situation. Schools as a key organisation in surviving any environment changes need to adapt and adjust. On the other hand, schools are viewed as conventional institutions. Comfortable with a traditional approach in managing the organization, schools consider as one of the latter in implementing change management. Lack of discussion and research related to agility in schools, particularly kindergarten to high school (K12) setting encourage this article to conduct a case study in one of the fastest growing schools in Indonesia namely Sekolah Murid Merdeka (SMM). This article was conducted using a qualitative method complemented with a survey as triangulation approach. The result from this research is that SMM argues to be implementing agility as a key variable in executing the operational system. Agility became a significant dimension in helping SMM adjust with the current environment and market demand thus resulted in gaining almost 10000 students in one year.